Rubber wall damper element for reinforced concrete and steel frame building structures - Mohd Zain, Mohd Azmi (2017)
The application of modern control techniques to diminish the effects of dynamic loads on building structures offers an appealing alternative to traditional design approaches. Rubber Wall damper (RWD) is one of the inventive passive energy dissipation device which enhance lateral resistance capacity and damping characteristic of the structures. RWD similar to fluid infill supplemental wall dampers yet is more suited for use in far field earthquake zone and is less expensive, maintenance free and economy. Here, a RWD is fabricated using Malaysian rubber, local steel and reinforced concrete structure, to reduce dynamic load effect and preclude vibration damage of buildings. Critical review of literature indicates no analytical model available for numerical model of RWD in building structure. Furthermore, the building frames response analysis is realistic, only if nonlinearity due to material behavior is also taken into account. Thus, nonlinear dynamic analysis is a prelude to achieving both accuracy and economy in the structural design. The analytical and constitutive model for RWD are developed for purpose of numerical modeling and finite element simulation and evaluate effect of Damper in seismic response of structures. Various types of concrete framed buildings equipped by proposed device are analyzed and efficiencies of device was assessed. Additionally, through nonlinear dynamic analysis, the possibilities of arresting plastic hinge formations in structural components were investigated. The numerical analysis results showed the maximum horizontal displacement of frames with RWD diminished from 45% range up to 92%. Generally, the maximum story displacements dropped dramatically compared to similar response of the bare frame system. In steel frame and Reinforced Concrete frames furnished by the RWD device, the maximum failure capacity improved approximately by 256% and 244% respectively. This proved the effectiveness of developed RWD device energy dissipation option in the buildings. Besides the numerical analysis, the prototype damper device has been fabricated and experimental test has been carried out to assess the functionality and performance of the developed adaptive systems with conventional systems. Experimental test results on prototypes steel and reinforced concrete frame subjected to cyclic displacement action, verified the efficiency of the RWD device, whenever implemented in to the bare frame. The ductility behaviour and failure mechanism are enhanced in both frame systems. The results proved performance of moment resistance frame furnished by above devices has been improved noticeable and the damper device is able to increase safety of building against severe earthquakes.